Conditional Contribution Mechanisms for the Provision of Public Goods in Dynamic Settings - Theory and Experimental Evidence - Andreas Reischmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Many mechanisms have been developed to solve the free-rider problem in private public good provision. Most of these mechanisms were designed to have good static (Nash) equilibrium properties. I present in this paper a new class of mechanisms, the Conditional Contribution Mechanisms (CCM), which are designed to have good dynamic equilibrium properties instead. The CCMs give all agents the possibility to condition their contribution on the total level of contribution provided by all agents. Their dynamic incentive structure makes the CCMs particularly suited for repeated public goods. I prove for a very general class of environments that all equilibria of the CCMs under a new variant of Better Response Dynamics, called Unexploitable Better Response Dynamics (UBRD), are Pareto efficient. I further present a first experimental study of one mechanism's performance compared to the performance of the Voluntary Contribution Mechanism. In an environment with binary contribution and linear valuations, agents play the mechanisms in a repeated setting. I test one case of complete information and homogeneous valuations and a second case with incomplete information and heterogeneous valuations. In both cases a significantly higher contribution rate can be observed when the CCM is used. Furthermore, all stable outcomes of the CCM, which are observed in the experiment, are in line with the prediction of UBRD.
Keywords: H41; D82; C92; 330